Physicochemical Properties, Structural Characterization, Immunoenhancing and Hypoglycemic Activities of Fucoidan Extracts from Two Sargassums Species - CHEN Shutong, ZHOU Qingling, YANG Ruiyu, WANG Xiaoxiao, DING Rui, LI Rui, LUO Lianxiang, ZHONG Saiyi, (Shipin Kexue, 2024)
In this study, the chemical compositions, structures, immunomodulatory and hypoglycemic activities of fucoidans from Sargassum zhangii (SZ-Fuc) and Sargassum hemiphylla (SH-Fuc) were analyzed and compared. The results showed that the sulfate group content and molecular mass of SZ-Fuc were (29.74 ± 0.01)% and 111.28 kDa, respectively, and SZ-Fuc had a relatively loose surface structure. The main chain of SZ-Fuc was composed of (→1) linked fucose, xylose, glucose, mannose and galactose, (1→3)- and (1→4)- linked xylose, (1→2)-linked mannose, (1→3)-, (1→4)- and (1→6)-linked galactose, and (1→4)- and (1→6)-linked glucose. Meanwhile, the sulfate group content and molecular mass of SH-Fuc were (44.11 ± 0.01)% and 1 166.48 kDa, respectively, SH-Fuc had a compact surface structure, and its main chain contained (→1), (1→3)- and (1→4)-linked fucose, (→1), (1→4)- and (1→6)-linked glucose, (→1) and (1→2)-linked mannose, and (1→4)-linked galactose. Besides, both SZ-Fuc and SH-Fuc had branched structures. They significantly increased NO release from RAW264.7 cells and improved the protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2), indicating good immunomodulatory activity. The immunomodulatory activity of SZ-Fuc was better than that of SH-Fuc, while the inhibitory effect of SH-Fuc on α-glucosidase was better than that of SZ-Fuc, suggesting that SH-Fuc had better hypoglycemic potential. This study can provide a theoretical basis for polysaccharides from S. zhangii and S. hemiphylla in the development of functional and nutritional foods with immunomodulatory and blood glucose-reducing activity.